2018
DOI: 10.1103/physrevb.98.081103
|View full text |Cite
|
Sign up to set email alerts
|

Planar Hall effect in the type-II Dirac semimetal VAl3

Abstract: The study of electronic properties in topological systems is one of the most fascinating topics in condensed matter physics, which has generated enormous interests in recent times. New materials are frequently being proposed and investigated to identify their non-trivial band structure. While sophisticated techniques such as angle-resolved photoemission spectroscopy have become popular to map the energy-momentum relation, the transport experiments lack any direct confirmation of Dirac and Weyl fermions in a sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 51 publications
(59 reference statements)
6
41
0
Order By: Relevance
“…In both cases, the field dependence of ρ ⊥ can be fitted to a power law function, i.e., ρ ⊥ ∝ B 1.57 and ρ ⊥ ∝ B 1.46 for the E //a and E //b axes, respectively. Both MR follow subquadratic field dependence [38], and the power exponents are quite close to those observed in other systems [20,21,23]. Previous work showed that the mobility in WTe 2 was highly anisotropic [34], resulting in a highly anisotropic conductivity (σ = neμ) and a strong anisotropic magnetoresistance in WTe 2 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In both cases, the field dependence of ρ ⊥ can be fitted to a power law function, i.e., ρ ⊥ ∝ B 1.57 and ρ ⊥ ∝ B 1.46 for the E //a and E //b axes, respectively. Both MR follow subquadratic field dependence [38], and the power exponents are quite close to those observed in other systems [20,21,23]. Previous work showed that the mobility in WTe 2 was highly anisotropic [34], resulting in a highly anisotropic conductivity (σ = neμ) and a strong anisotropic magnetoresistance in WTe 2 .…”
Section: Resultssupporting
confidence: 79%
“…Since the prediction of theoretical work, the giant PHE has been observed in several Dirac/type-I Weyl semimetals, such as ZrTe 5 , and GdPtBi [17][18][19][20]. Although several studies report observing a chiral-anomaly-induced PHE in type-II Dirac/Weyl semimetals, e.g., VAl 3 and WTe 2 [21,22], the strong orbital magnetoresistance (OMR) in type-II Weyl makes it challenging to know, with certainty, the real physical origin of the observed PHE [23].…”
Section: Introductionmentioning
confidence: 98%
“…The extracted value of the exponents for the two cases is found to be nearly quadratic (n = 2) for both ∆ρ chiral and ρ ⊥ . These values are similar to exponents obtained for other DSM and WSM materials 33 .…”
Section: (A) and Longitudinal Mr (B I) At Various Temperatures As Shosupporting
confidence: 89%
“…For example, the NLMR as a signature of the chiral anomaly, may be masked by other contributions, both intrinsic like orbital MR or extrinsic like current jetting effects. On the other hand, recent experimental findings suggest that PHE can be observed even if signature of the chiral anomaly are masked by other contributions because the PHE does not depend on the position of the chemical potential from the Weyl nodes 33,37 . This implies that, irrespective of the position of the chemical potential and even in the presence of extrinsic effects, topological bands can still contribute to special transport effects such as PHE and therefore contributions of these topologically non-trivial bands can be probed by measurements other than NLMR.…”
Section: Introductionmentioning
confidence: 98%
“…Very recently, the current authors along with others, proposed the planar Hall effect (PHE) 72,73 as another striking consequence of chiral anomaly in WSMs, where the effect manifests itself when the applied current, magnetic field, and the induced transverse Hall voltage all lie in the same plane, precisely in a configuration in which the conventional Hall effect vanishes. This resulted in a series of experiments, where this effect was confirmed by several groups [74][75][76][77][78][79][80][81][82][83][84][85] in Weyl and Dirac semimetals.…”
Section: Introductionmentioning
confidence: 87%